Financial Literacy and Digital Payment Adoption as Economic Drivers of Consumer Shopping Behavior and Self-Control - Purwaningtyas, Purwaningtyas; Sari, Dhany Efita (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of financial literacy, digital payment usage, and self-control on shopping habits. Data were collected through questionnaires distributed to respondents and analyzed using path analysis with SmartPLS. The results indicate that financial literacy and self-control have a negative and significant effect on shopping habits, while digital payment usage has a positive and significant influence. The financial literacy coefficient of -0.122 and self-control coefficient of -0.113 suggest that an increase in these variables reduces shopping habits. Conversely, digital payment usage, with a coefficient of 0.546, shows that the more frequently digital payments are used, the higher the individual's shopping habits. These findings highlight the crucial role of financial literacy and self-control in curbing consumer behavior, while the convenience of digital transactions tends to increase shopping frequency. This study contributes to the development of financial education strategies and consumer behavior management in the digital era.